Comparative pathogenicity of sexual and asexual spores of Zymoseptoria tritici (septoria tritici blotch) on wheat leaves. (10th April 2015) - Morais, D.; Laval, V.; Sache, I.; Suffert, F.
Abstract : Zymoseptoria tritici ascospores and pycnidiospores are considered the main forms of primary and secondary inoculum, respectively, in septoria tritici blotch epidemics. The pathogenicity of the two types of spores of the same genotypic origin were compared through a two‐stage inoculation procedure in controlled conditions. Adult wheat leaves were inoculated with ascospores collected from field sources, yielding 119 lesions; pycnidiospores collected from 12 lesions resulting from these ascospore infections were then used for inoculation. Lesion development was assessed for 5 weeks; latent period, lesion size, and pycnidium density were estimated for different isolates. The latent period was calculated as the maximum likely time elapsed between inoculation and either the appearance of the majority of the sporulating lesions (leaf scale) or the appearance of the first pycnidia (lesion scale). The latent period was significantly longer ( c . 60 degree‐days, i.e. 3–4 days) after infection with ascospores than with pycnidiospores. No difference was established for lesion size and density of pycnidia. A comparison with other ascomycete fungi suggested that the difference in latent period might be related to the volume of spores and their ability to cause infection. Fungal growth before the appearance of lesions may be slower after inoculation with an ascospore than with a pycnidiospore. The mean latent period during the very beginning of epidemics, when first lesions are mainly caused by ascospores, may be longer than during spring, when secondary infections are caused by pycnidiospores. Disease models would be improved if these differences were considered.